Analysis of atomic beam collimation by laser cooling - Li, Shangyan (Sci Rep, 2018)
The collimation of a thermal atomic ytterbium beam utilizing a two-dimensional optical molasses is analysed by employing the Monte Carlo simulation. The dependencies of the collimation efficiency on power, frequency detuning and beam size of the laser are studied for various conditions, especially for the case of an imbalanced laser intensity and an impure laser polarization. The influences of these imperfect factors are discussed, and the lowest transverse temperature by the collimation in the experiment is evaluated.